The Use of Dictogloss Technique in Teaching Writing of Procedure Text - Rohaniyah, Jaftiyatur; Nisak, Khairatun (Universitas Nurul Jadid, 2019)
Writing is a skill which is consider as difficult skill in teaching learning process because it need an effort to collect ideas and words on the paper. Most of student said that writing process is very difficult and often make them lazy and bored to write and to make student motivated and enthusiastic to study the teachers probably have the strategy, method or a technique to teach their students and this research attempt to describe the Dictogloss technique that is implemented by the teacher in teaching writing of procedure text in the ninth grade of SMPI Bahrul-Huda sumber anyar. From this research, the researcher want to know the process of dictogloss technique and the advantage of that technique in writing material. In this research, the resercher use qualitative approach. Data collection procedures that used in this research are observation, interview, and documentation. The result show that implementation of Dictogloss technique that is implemented by the teacher in the class room is run well and teaching learning process is successful by using the technique. Students get progress to write than before and they get many vocabularies as guided writing, they also know how to arrange words to be sentence then write it to be one paragraph but in the other side the technique is need much time and sometimes it affect student in learning.